The Social Implications of Warehouse Automation: Balancing Efficiency and Employment - Garaga, Swetha (International Journal of Computing and Engineering, 2025)
Warehouse automation technologies continue to change global supply chains and significantly improve operational efficiency by creating complex employment challenges. This comprehensive study examines the versatile social implications of this technical revolution, including productivity, profit and workforce disruptions in the logistics sector. The evaluation includes operational performance enhancement, including better accuracy, processing speed, and workplace protection and documents the pattern of employment displacement that affects some demographic groups and geographical areas. Notably, emerging human-automatic integration models leverage complementary capabilities by preserving employment opportunities through strategic job redistributions. This study evaluates the workforce adaptation strategies, highlighting the effectiveness of successful training programs and facilitating career advancement structures that facilitate successful transitions. Additionally, policy interventions are evaluated, including educational improvement, social security net adaptation, and economic incentives that balance technological progress with workforce stability. These findings provide a foundation for developing a balanced approach that maximizes the benefits of automation by reducing negative effects on employment.